South African transfer pricing income tax legislation: is there still a gap? - Garach Bhaga Muljee, Trisha (My University, 2017)
Transfer pricing is a continuously evolving phenomenon and is a topical issue world-wide. With increasing inter-company cross-border transactions, multinational enterprises are using loopholes in the interaction of tax legislation of different countries as a tool to shift profits to a more favourable jurisdiction, thereby avoiding tax in the jurisdiction in which they are resident and eroding the resident jurisdiction’s tax base. This research report examines and discusses the substituted South African transfer pricing legislation that applies for the years of assessment commencing on or after 1 April 2012 as well as the related SARS guidance. An analysis of transfer pricing legislation and guidelines in three selected countries and the OECD transfer pricing guidelines will also be performed. The comparisons of the legislation and guidelines will highlight whether there are still weaknesses in the South African transfer pricing legislation and will indicate possible solutions to these weaknesses which will assist in reducing the erosion of the South African tax base. Key words: Tax, Transfer pricing, Tax avoidance, Base erosion and profit shifting, Multinational enterprises (‘MNEs’), South African Revenue Service (‘SARS’), Organisation for Economic Co-operation and Development (‘OECD’).
A research report to be submitted to the Faculty of Commerce, Law and Management in partial fulfilment of the requirements for the degree of Master of Commerce (specialising in Taxation), Johannesburg, 2017
Keywords: Transfer pricing--Law and legislation--South Africa; International business enterprises--Taxation--Law and legislation--South Africa; Taxation--Law and legislation--South Africa